Kualitas Air, Pertumbuhan dan Kelulushidupan Benih Abalone (Haliotis squamata) dengan Aplikasi RAS di BPIUUK Karangasem Bali - Akbar, Arief Prayoga; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Bumi Lestari, 2022)
Abalone is one of the sea snails that have high economic value and has advantages because it has a high protein content of 71.99%, a fat content of 3.24%, and can be used as medicine. The high demand for abalone causes the increase of wild capture and lead to scarcity of abalone in the waters. One way to overcome this problem is by cultivate the abalone. Abalone cultivation can be done with a monoculture system. One of the technologies applied is by using a recirculation aquaculture system (RAS), which is reprocessing the water used so that it can be reused for cultivation activities. The purpose of this study was to analyze the parameters of water quality, growth length, weight and survival of abalone (Haliotis squamata) seeds using the RAS system. The research was conducted in June – September 2020 at the Shrimp and Shellfish Parent Center, Karangasem, Bali. The research was performed by purposive sampling method. The water quality parameters data such as nitrite, ammonia, TSS pH, temperature, DO, and salinity were taken. The results of the measurement of water quality are nitrite 0 – 0.338 mg/L, ammonia 0 – 0.09 mg/L, TSS 0 – 15 mg/L, pH 7 – 8, temperature 26 – 28 oC, DO 4.3 – 7.07 mg/L, and salinity 31 – 38 ppt. Those values are still in the optimal range for abalone culture. The growth in length and absolute weight of abalone seeds during the study were 25.17 mm/ind. and 9.15 g/ind., respectively, and the survival value was 99.5% during the 100-day culture period.